Zamien postać ogolna na kanoniczna, pełne rozwiązania

a) y= -4x^2+6x+1
b) y=-3x^2+4x+3

zamien postać kanoniczna na ogolna
a) y=2(x-1)^2+5
y=-3(x+4)^2+2
b) y= -1(x-2)^2+3


Odpowiedź :

Odpowiedź:

1.

a)

y = -  4x² + 6x  + 1

a  = - 4 ,  b = 6 , c = 1

Δ =  b² - 4ac  = 6² - 4  * (- 4) *  1 = 36 + 16 = 52

p = - b/2a = - 6/(- 8) =  6/8  = 3/4

q  =  -  Δ/4a = -  52/(- 16) = 52/16 = 3 4/16 = 3 1/4

Postać kanoniczna

y = a(x - p)²  + q  = - 4(x - 3/4)² + 3 1/4

b)

y = -  3x² + 4x + 3

a = - 3 ,  b = 4 , c = 3

Δ = b² - 4ac = 4² - 4 * (- 3) * 3 = 16 + 36 = 52

p = -  b/2a = - 4/(- 6) = 4/6 = 2/3

q = - Δ/4a = - 52/(- 12) = 52/12 = 4 4/12  =  4 1/3

Postać kanoniczna

y = a(x - p)² + q = -  3(x - 2/3)² + 4 1/3

2.

a)

y = 2(x - 1)² + 5 = 2(x² - 2x  + 1) +  5 = 2x² - 4x + 2  + 5 = 2x² - 4x + 7

y = - 3(x + 4)² + 2 = - 3(x² + 8x +  16) + 2 = - 3x²  - 24x - 48 + 2 =

= - 3x²  - 24x - 46

b)

y = -  1(x - 2)² + 3 = - (x² - 4x  + 4) + 3 = - x² + 4x - 4 + 3 = - x² + 4x - 1